Global city : Malay motion pictures, Mambang Moden and the contested terrains of Singapore history / Benjamin McKay - McKay, Benjamin (UPENA, 2006)
This article explores the manner in which local filmmakers and audiences synthesised and localised their engagement with postwar consumer affluence - real and imagined. The rise of popular magazines, access to a burgeoning and global "youth" culture, the popularity of rock and roll and the adoption of fashion garments that embodied these changes led to new modes of Singaporean selfprojection and identity. Local cuisine - always an important part of the city-state's identity - was transformed. The meal itself became as much an act of leisure as attending movies, reading popular magazines and adorning oneself with the latest fashions. This article asserts that the reinvention of Singaporean selfprojection in the period 1955-1970 is directly related to the variety and breadth of available cinematic culture - both local and imported. A rising middle class and a relatively youthful population "Singaporeanised" a sense of global style that has become synonymous with our broader nostalgic reflections of the nineteen fifties and sixties. The article concludes by looking at the manner in 115 Jurnal Skrin Malaysia which contemporary Singapore addresses the legacy of that time and its popular culture - as both nostalgia and for the purpose of the nation-building enterprise.